Role FtsH proteas v sinici Synechocystis sp. PCC 6803 - Krynická, Vendula (Jihočeská univerzita, 2015)
FtsH, proteázy, Synechocystis, membránový protein, kontrola kvality proteinů, PSII, Fur, regulace transkripčních faktorů
Role of FtsH proteases in the cyanobacterium Synechocystis sp. PCC 6803
Keywords: FtsH; proteases; Synechocystis; membrane; photosynthesis; quality control; PSII; Fur; transcriptional factor regulation; FtsH; proteases; Synechocystis; membrane; photosynthesis; quality control; PSII; Fur; transcriptional factor regulation